Existential insecurity and deference to authority: the pandemic as a natural experiment - Foa, Roberto Stefan; Welzel, Christian (Frontiers in Political Science, 2023)
Introduction The global coronavirus pandemic offers a quasi-experimental setting for understanding the impact of sudden exposure to heightened existential risk upon both individual and societal values. Methods We examined the effect of the pandemic on political attitudes by comparing data from eight countries surveyed before and after the worldwide spread of COVID-19 in March 2020 with continuous weekly polling tracker data from the United Kingdom from 2019 to 2021. Multilevel models were used to explore the drivers of change, and the results indicated that reported emotions of fear and stress were positively associated with institutional approval during periods of greater pathogen risk. Results Our findings revealed that support for political and technocratic authority, as well as satisfaction with political institutions, rose significantly above long-term historical baselines during the pandemic. Discussion The results support the hypothesis that exposure to existential risk results in greater support for authority and that individual feelings of insecurity may be linked to less critical citizen orientations.